Consumer acceptance of cultured meat: an empirical analysis of the role of organizational factors - Nick Lin-Hi; Marlene Reimer; Katharina Schäfer; Johanna Böttcher (Journal of Business Economics, 2022)
Cultured meat, i.e. meat produced in-vitro through the cultivation of animal stem cells, is a radical innovation that prepares to enter the market in the near future. It has the potential to substantially reduce the negative externalities of today's meat production and consumption and pave the way for a more sustainable global food system. However, this potential can only be realized if cultured meat penetrates the mass-market, which renders consumer acceptance a critical bottleneck. Using structural equation modeling, the present paper investigates the role of hitherto neglected organizational factors (trustworthiness, corporate social responsibility (CSR), and extrinsic motives) as antecedents of consumer acceptance of cultured meat. To this end, a pre-post intervention design in terms of a two-part online questionnaire was used with the final sample consisting of 966 participants. We found that in addition to established antecedents on the product level, organizational trustworthiness and CSR have a significant influence on consumers' willingness to buy cultured meat. The findings indicate that organizational factors matter for consumer acceptance of cultured meat.
Keywords: M1; O3; Q1; Q01; 650; Consumer acceptance; Cultured meat; Food system; CSR; Trustworthiness; Willingness to buy; Sustainability